Impacto dos problemas de saúde bucal na qualidade de vida de gestantes - Rosell, Fernanda Lopez; Oliveira, Ana Luísa Botta Martins de; Tagliaferro, Elaine Pereira da Silva [UNESP]; Silva, Silvio Rocha Corrêa da [UNESP]; Valsecki Júnior, Aylton (My University, 2013)
Objectives: 1) to evaluate the impact of oral health problems on the quality of life of pregnant women by the simplified Oral Health Impact Profile (OHIP-14) questionnaire as well by the presence of dental caries, periodontal disease and denture use/need; 2) to correlate the sociodemographic variables and the oral health conditions revealed in the clinical examinations with the OHIP-14. Method: In addition to the application of the OHIP-14 questionnaire, clinical examination of the oral conditions (CPI - community periodontal index, DMFT and prosthetic evaluation) was performed on 51 pregnant women, who sought dental treatment between April 2008 and August 2010 at the Preventive Dentistry Clinic. Descriptive analyses were made for sample characterization, bivariate analysis (chi-square or Fisher’s exact tests) and multiple logistic regressions at a 5% significance level to assess the correlation between the impact of oral health on the quality of life of pregnant women and the socio-demographic and clinical variables. Results: The OHIP-14 data showed a lesser impact of oral health on the women’s quality of life. The mean DMFT was 12.8; 70.6% of the pregnant women presented dental calculus and 58.8% needed prostheses. The association between OHIP-14 data and last dental visit and DMFT remained in the final regression model (p<0.05). Conclusion: Caries experience of the pregnant women was considered high. Most of them needed prostheses and presented dental calculus. The OHIP-14 presented a low impact on this population and was significantly influenced by the last dental visit and the DMFT index.

Objetivos: 1) Avaliar o impacto dos problemas de saúde bucal na qualidade de vida de gestantes por meio do questionário OHIP-14, bem como a presença de cárie dentária, doença periodontal e uso e necessidades de próteses em gestantes; 2) associar as variáveis sociodemográficas e condições de saúde bucal encontradas no exame clínico com o OHIP-14. Métodos: Além da aplicação do questionário OHIP-14, realizou-se uma avaliação clínica das condições bucais (índices: IPC, CPO-D e avaliação protética) em 51 gestantes que procuraram atendimento odontológico junto à Clínica de Odontologia Preventiva, no período de abril de 2008 a agosto de 2010. Realizaram-se análises descritivas para caracterização da amostra, análise bivariada (teste de Qui-Quadrado ou Exato de Fisher) e regressão logística múltipla em nível de significância de 5% para analisar a associação entre o impacto da saúde bucal na qualidade de vida de gestantes e as variáveis sociodemográficas e clínicas. Resultados: Os dados do OHIP-14 mostraram menor impacto da saúde bucal na qualidade de vida. O CPOD médio foi 12,8; 70,6% das gestantes apresentavam cálculo dental e 58,8% necessitavam de prótese. A associação entre OHIP-14 e última visita ao dentista e CPOD permaneceram no modelo final de regressão (p<0,05). Conclusão: A experiência de cárie das gestantes examinadas foi considerada alta, a maioria apresentava necessidade de prótese e presença de cálculo dental. O OHIP apresentou baixo impacto no grupo estudado e foi significativamente influenciado pela última visita ao dentista e pelo índice CPOD.
Impact of oral health problems on the quality of life of pregnant women
Keywords: Oral health; Pregnancy; Quality of life; Saúde bucal; Gravidez; Qualidade de vida